Supporting the process of developing and managing LOM application profiles: The ASK-LOM-AP tool - Sampson, Demetrios; Zervas, P.; Chloros, G. (2012)
A number of international initiatives, such as the Open Educational Resources initiative, have recognized the potential value of sharing and reusing digital resources among educational communities. As a result, organizing, offering, and accessing these resources over the web have been key issues for both the research and the educational community. Within this framework, a popular way for describing digital educational resources is the IEEE Learning Object Metadata (LOM) Standard. On the other hand, it has been also recognized that it is not possible for a generic standard such as IEEE LOM to fully meet the specific requirements and accommodate the particular needs of different educational communities. Therefore, the practice of generating Application Profiles (APs) of the IEEE LOM has emerged and a number of different APs have been developed worldwide. However, despite the widespread development of APs it seems that only a limited number of software tools exist, to support the process of LOM Application Profiling. Within this context, in this paper we target addressing this problem by introducing a new web-based tool (ASK-LOM-AP) that aims to overcome the identified limitations of existing tools and facilitate its users to easily develop and manage LOM APs for different educational communities. © 2008-2011 IEEE.